2019
DOI: 10.1088/1361-6560/ab2a22
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of quantitative SPECT/CT using NEMA NU 2 PET methodology

Abstract: Although PET is routinely evaluated using NEMA NU2 as standard in the clinic, standard methodology for evaluating the performance of quantitative SPECT systems has not been established. In this study, the quantitative performance of the Symbia Intevo SPECT/CT was evaluated for two common isotopes (99mTc, 177Lu) and benchmarked against the performance of a PET/CT. A further aim was to demonstrate the utility of adapting NEMA NU2 PET measurements to SPECT. In addition, dead-time and resolution recovery were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 30 publications
3
31
2
Order By: Relevance
“…Although a 42% isocontour method shows good recovery for both PET [36] and SPECT [13], the background-corrected 50% isocontour method was chosen because of its high repeatability for PET in a multicenter settings [37] and to align our results as much as possible with the already existing standards for PET quantification [38]. However, a recently published study by Ryu et al [39] showed that the line profiles over active spheres of reconstructed SPECT images (using 99m Tc and 177 Lu) showed a very different profile than the same spheres measured on PET (using 18 F and 68 Ga). This indicates that a 50% isocontour method might not be the most ideal solution threshold for contouring in SPECT and that a lower threshold might be more appropriate as demonstrated by Collarino et al [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although a 42% isocontour method shows good recovery for both PET [36] and SPECT [13], the background-corrected 50% isocontour method was chosen because of its high repeatability for PET in a multicenter settings [37] and to align our results as much as possible with the already existing standards for PET quantification [38]. However, a recently published study by Ryu et al [39] showed that the line profiles over active spheres of reconstructed SPECT images (using 99m Tc and 177 Lu) showed a very different profile than the same spheres measured on PET (using 18 F and 68 Ga). This indicates that a 50% isocontour method might not be the most ideal solution threshold for contouring in SPECT and that a lower threshold might be more appropriate as demonstrated by Collarino et al [13].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative SPECT/CT imaging with radiotracers such as gallium-67 and lutetium-177 is available today (42,43). A signi cant limitation on its value in determining lesion dosimetry, however, is the poor spatial resolution in SPECT/CT using a medium energy collimator with values of 20+ mm FWHM in clinical imaging (44). This introduces a signi cant partial volume effect (PVE) whereby the radioconcentration is underestimated by a signi cant amount in regions less than 2.5-3 the spatial resolution, that is, 50-60 mm.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed that quantitative SPECT should be subject to the same NEMA NU 2 QC process as PET. 33 If quantitative SPECT is to be used for progress assessment the reproducibility of measurements in individuals with ATTR-CM must be assessed. Larger clinical trials need to be undertaken to determine whether quantitative SPECT measurements can provide prognostic information in ATTR or play a role in assessing disease progression and treatment response.…”
Section: The Future Of Quantitative Bone Scansmentioning
confidence: 99%